Continuity of Tradition Dance: Acedemiciansâ Intervention on Artists and Performing Arts Groups - Indrayuda, Indrayuda (Harmonia: Journal of Arts Research and Education, 2015)
This article intends to uncover a concept of developing tradition-art groups in West Sumatra, which is considered that they have been left behind by modern-art groups in terms of packing aspect, presentation, and technical skills. Hence, this article reveals intervention of the academician in developing and providing support in the forms of improving skills and knowledge of the artists and art groups. The support includes improving skills and knowledge of expressing arts through giving packing techniques and arranging art performance, orientated toward educational and social extension actions. The knowledge may consist of techniques for developing movements, dance music, costumes, and make-up affecting skills of arranging and packing performance arts that can be divested in art industries. The method used in this investigation was games that aimed to cope with boredom and improve new awareness of concepts of how to pack performance arts. In addition, the case study was employed to solve problems faced by partners in the field. Moreover, practices about how to pack the arts were critical to be done through brainstorming, discussing, and lecturing.